2018
DOI: 10.12973/iji.2018.1139a
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Numbered Heads Together-Assurance Relevance Interest Assessment Satisfaction on Students’ Motivation

Abstract: The purpose of this study was to investigate the effects of the Assurance Relevance Interest Assessment Satisfaction (ARIAS) strategies set with Numbered Heads Together (NHT) on students' learning motivation. This quasi experimental study employed a pretest-post test nonequivalent control group design. The population of the research was all the eleventh graders who were enrolled in the science classes of public senior high schools (SMA) in Makassar, Indonesia. There were 21 schools in total. Random sampling te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
(12 reference statements)
1
12
0
6
Order By: Relevance
“…This participation in the classroom is mainly affected by motivation. Chiang & Lee (2016) state that student's learning motivation can be stimulated by learning model (as cited in Mustami & Safitri (2018)). Lestari (2019) and Anggareni & Wulanjani (2017) point out that the use of technology takes an important role in teaching and learning process on this era of 21st century of learning.…”
Section: Sonita and Febriamentioning
confidence: 99%
See 2 more Smart Citations
“…This participation in the classroom is mainly affected by motivation. Chiang & Lee (2016) state that student's learning motivation can be stimulated by learning model (as cited in Mustami & Safitri (2018)). Lestari (2019) and Anggareni & Wulanjani (2017) point out that the use of technology takes an important role in teaching and learning process on this era of 21st century of learning.…”
Section: Sonita and Febriamentioning
confidence: 99%
“…Cooperative learning is a group of students' relationship that requires individual accountability, positive interdependence, interpersonal, face-to-face promotive interaction, skills, and processing which called the five basic elements of cooperative learning (Wang, 2020). According to Mustami & Safitri (2018), cooperative learning model is one of learning models that has been developed and confirmed to improve students' performance due to its design to facilitate students' cooperation and dependence on each other in completing a task or purpose.…”
Section: Sonita and Febriamentioning
confidence: 99%
See 1 more Smart Citation
“…Indikator kemampuan kerja sama dapat dilihat dari 5 hal penting, yaitu: menjawab dan saling membantu. (Mustami, Khalifah, & Safitri, 2018) Melalui pembelajaran kooperatif tipe STAD ditemukan adanya peningkatan pada kemampuan kerja sama dan hasil belajar siswa sehingga STAD dapat dijadikan sebagai salah satu pilihan pembelajaran yang menekankan pada kegiatan kelompok sehingga dapat meningkatkan kerja sama siswa. Dengan demikian dapat disimpulkan bahwa terdapat berbagai macam upaya untuk meningkatkan kemampuan kerja sama siswa di mana karakteristik dari siswa serta masalah yang terjadi pada tiap tempat juga menjadi faktor pendukung dalam menentukan jenis upaya yang akan diberikan.…”
Section: Pentingnya Kerja Sama Dalam Pendidikanunclassified
“…The research results by Darmawati (2013) showed that learning motivation had a significant effect on the learning achievement of senior high school students in Tuban. Mustami and Safitri (2018) stated that learning motivation playing the main important role in determining student learning result because motivation is the key process to predict intensity, pathway, and effort to achieve students` objectives.…”
Section: Introductionmentioning
confidence: 99%